Voltammetric Determination of Praziquantel in Tablets and Biological Fluids - Rizk, Mohammed; Belal, Fathalla; Ibrahim, Fawzia; Ahmed, Soad; El-Enany, Nahed M. (Arzneimittelforschung, 2001)
A simple method is described for the determination of praziquantel (CAS 55268-74-1) in its pure form, tablet formulations and biological fluids. The proposed method depends upon the polarographic activity of praziquantel at the dropping mercury electrode (DME) in Britton Robinson buffers, whereby a well-defined catholic wave is produced over the pH range 7–12. The wave was characterized as being irreversible diffusion-controlled with limited adsorption properties. The diffusion current constant (Id) was 0.56 ± 0.004 (n = 11). The current-concentration relationship was found to be rectilinear over the range 8–48, 3.2–38.4 and 0.48-20 μg · ml−1 using direct current (DCt), differential pulse polarographic (DPP) and alternating current (ACt) odes, respectively, with minimum detection limit (S/N = 2) of 0.32 μg · ml−1 (1.02 × 10−6 mol/l and 0.02 μg · ml−1 (6.4 × 10−8 mol/l) for DPP and ACt modes respectively. The average percent recovery was favourably compared to a reference method with a satisfactory standard deviation. The proposed method was applied to spiked human urine and plasma. The percentage recoveries were 99.33 ± 0.79 and 98.23 ± 0.53, respectively.
Keywords: CAS 55268-74-1; Praziquantel, determination in tablets and biological fluids